Preliminary results of spot-stent grafting in Stanford type B aortic dissection and intramural haematoma - Meisenbacher, Katrin; Böckler, Dittmar; Geisbüsch, Philipp; Hank, Thomas; Bischoff, Moritz (European journal of cardio-thoracic surgery, 2020)
Optimal treatment for patients with diseased proximal landing zones in acute/subacute Stanford type B dissection and intramural haematoma remains unclear. This study describes the preliminary outcomes of a localized endovascular treatment [spot-stent grafting (SSG)] of main entries/intramural blood pooling located downstream (aortic zones 4 and 5) using one single short device comprising diseased landing zones, looking particularly at the technical and morphological outcomes.Patients undergoing thoracic endovascular aortic repair (TEVAR) for acute/subacute aortic dissection Stanford type B/intramural haematoma Stanford type B between 1997 and 2018 were identified from a prospectively maintained institutional database. In a total of 183 cases, 22 patients (7 women; median age 62 years; range 35-79 years) received SSG. The primary study end point was technical success. The primary morphological end point was false lumen thrombosis/aortic remodelling. Secondary end points were TEVAR-related mortality/morbidity and reinterventions. The median follow-up was 28.5 months (5 days-15.6 years).The primary technical success rate was 100% (22/22). During follow-up, false lumen thrombosis was seen in 21 patients (95.5%) at a median of 6 days (0 days to 2.7 years) after the index procedure (limited/extended false lumen thrombosis: n = 9 vs 12). Aortic remodelling was achieved in 15 of 22 patients (68.2%) at a median of 360 days (3 days to 7.2 years). Limited/extended remodelling was observed in 8/15 and 7/15, respectively. Retrograde dissection or stent graft-induced new entry was not observed. No stroke or spinal cord injury occurred. Reinterventions were performed in 4/22 cases. The in-hospital mortality and 30-day mortality were 0%. Overall mortality during the follow-up period was 22.7% (5/22).This study shows favourable technical and morphological results for SSG in selected patients with acute/subacute aortic dissection Stanford type B/intramural haematoma Stanford type B. Patient allocation to SSG remains individual. Prospective large-scale long-term data may allow refinement of the application.
Gesehen am 23.02.2021